1978
DOI: 10.1152/jn.1978.41.4.1026
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and potassium changes in extracellular microenvironment of cat cerebellar cortex

Abstract: 1. Local stimulus-evoked changes in concentration of extracellular calcium ions, [Ca2+]0, and potassium ions, [K+[0, were measured in the cerebellar cortex of the cat using paired ion-selected micropipettes. 2. Repetitive stimulation of 30 s duration decreased [Ca2+]0 from a base line of 1.2 mM to as low as 0.8 mM and increased [K+]0 from 3 mM to as much as 8 mM. The magnitude of the changes was directly related to stimulus frequency. Laminar analysis showed that the greatest ion changes occurred at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
135
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(147 citation statements)
references
References 0 publications
11
135
1
Order By: Relevance
“…Unlike other Ca 2þ -responsive agents, here we see a decrease in r 1 with the increase in Ca 2þ concentration. This behavior was expected to induce an increase in MR contrast following brain activation, since extracellular Ca 2þ concentration is reduced during neuronal depolarization (27)…”
Section: Resultsmentioning
confidence: 99%
“…Unlike other Ca 2þ -responsive agents, here we see a decrease in r 1 with the increase in Ca 2þ concentration. This behavior was expected to induce an increase in MR contrast following brain activation, since extracellular Ca 2þ concentration is reduced during neuronal depolarization (27)…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been reported that pathological conditions such as ischemia or spreading depression lead to large elevations of extracellular K ϩ (60 -80 mM). These changes are accompanied by strong reductions in the concentration of extracellular C a 2ϩ (Nicholson et al, 1978). It has been suggested that the [C a 2ϩ ] i increase observed in astrocytes under these conditions is the result of C a 2ϩ influx through C a 2ϩ VOCs.…”
Section: Discussionmentioning
confidence: 98%
“…In cell culture, a wide range of Ca 2þ concentrations (even as low as 0.02 mM) are sometimes employed (12)(13)(14). Because cadherin structure is extremely sensitive to Ca 2þ ions, fluctuations in Ca 2þ concentration in the extracellular environment can influence the conformation of cadherin and ultimately affect their function (15)(16)(17)(18)(19)(20). While relatively small variations in Ca 2þ concentration are associated with disease pathology in vivo, more significant decreases (to~0.8 mM) were predicted in active synaptic clefts using simulations (21).…”
Section: Introductionmentioning
confidence: 99%
“…While relatively small variations in Ca 2þ concentration are associated with disease pathology in vivo, more significant decreases (to~0.8 mM) were predicted in active synaptic clefts using simulations (21). Furthermore, remarkable drops (as low as 0.3 mM) were identified experimentally in synaptic clefts during high frequency stimulation (19,20,22). At such low Ca 2þ concentrations, the binding of Ca 2þ would be significantly reduced, resulting in the loss of rigid cadherin ectodomain structure (23).…”
Section: Introductionmentioning
confidence: 99%